Comparación de los métodos tradicionales para cribado visual frente al prototipo de reglas de screening en estudiantes de optometría - Universidad Técnica de Babahoyo. Octubre 2024 - abril 2025. - Aguirre Guime, Jackeline Genesis (2025)
The research addresses the issue of traditional methods for visual screening in optometry, highlighting their effectiveness but also their limitations in cost, time, and portability. This particularly affects contexts with limited resources or rural areas. The main objective is to compare these traditional methods with a prototype of screening rules in optometry students from the Technical University of Babahoyo, evaluating accuracy, effectiveness, and ease of use. The methodology involved applying both approaches to a defined sample of students, collecting data on application times, diagnostic accuracy, and user feedback. This approach allowed for a detailed comparison of the two methods. The results showed that the screening rules prototype is more efficient, reducing application time and improving accessibility, while maintaining accuracy levels comparable to traditional methods. It is concluded that the prototype represents a viable alternative to optimize visual screenings, especially in resource-limited environments, and has the potential to improve both student learning and visual health coverage. Its implementation and continuous development are recommended.